Reduction of Zygosaccharomyces rouxii Population in Concentrated Grape Juices by Thermal Pasteurization and Hydrostatic High Pressure Processing - Rojo, María Cecilia; Cristiani, M.; Szerman, Natalia; Gonzalez, M.L.; Lerena, María Cecilia; Mercado, Laura Analia; Combina, Mariana (Springer, 2019)
Zygosaccharomyces rouxii is the most frequent spoilage yeast species detected in concentrated grape juice. In order to reduce Z. rouxii populations and consequently extend the microbiological shelf life of this product, different programs of thermal pasteurization and high hydrostatic pressures processing were evaluated. Results showed that pasteurization temperatures higher than 75 °C are necessary to reduce Z. rouxii population in concentrated grape juice. Reduction of 7 logarithms can be reached after 90 s at 75 and 80 °C, and 5 s at 85 °C of pasteurization treatment. High hydrostatic pressure treatment above 500 MPa for 2 min are necessary to reduce 7 logarithms of Z. rouxii population and to significantly extend the shelf life of concentrate grape juice. Extension of holding times from 3 to 5 min, at the different high hydrostatic pressures evaluated, did not improve the Z. rouxii population reduction, nor the shelf life extension of concentrate grape juice. In conclusion, thermal pasteurization and high hydrostatic pressure could be suitable treatments to achieve the reduction of Z. rouxii population below the recommendation limit (102 CFU/g) and extension of the microbiological shelf life of concentrate grape juice.